Julius, the Baby of the World - Henkes, Kevin (New York : Greenwillow Books, 1990)
Lilly is convinced that the arrival of her new baby brother is the worst thing that has happened in their house, until Cousin Garland comes to visit.
Keywords: Babies -- Fiction; Brothers and sisters -- Fiction; Mice -- Fiction; Infants -- Fiction